Differential effects of psychoactive substances on human wildtype and polymorphic T356M dopamine transporters (DAT). (15th June 2019) - Zwartsen, Anne; Litjens, Carlijn H.C.; Hondebrink, Laura; van den Heuvel, Jeroen J.M.W.; Greupink, Rick; Russel, Frans G.M.; de Lange, Dylan W.; Legler, Juliette; Koenderink, Jan B.; Westerink, Remco H.S.
Abstract: Many psychoactive substances affect the human dopamine (DA) reuptake transporter (hDAT). Polymorphisms in the encoding gene could affect the functionality of the transporter and consequently alter effects of psychotropic and recreational drugs. Recently, a T356 M single nucleotide polymorphism in the human SLC6A3 gene was described, which resulted in functional impairments of DA uptake. Therefore, we investigated the effects of 10 psychoactive substances (0.01–1000 μM)) on DA uptake in human embryonic kidney (HEK) 293 cells transiently overexpressing wildtype (WT) or T356 M hDAT. Our data shows that T356 M hDAT has a 3 times lower Vmax and a 3 times higher Km compared to WT hDAT. Additionally, all psychoactive substances inhibited DA uptake by T356 M and WT hDAT. The DA reuptake inhibitors (methylphenidate, cocaine, and bupropion) inhibited DA uptake by WT hDAT most potently, followed by amphetamine-type stimulants [4-fluoroamphetamine (4-FA), amphetamine and MDMA], selective serotonin reuptake inhibitors (SSRI; fluoxetine and citalopram) and arylcyclohexylamines [methoxetamine (MXE) and ketamine]. Compared to DA uptake by WT hDAT, bupropion, methylphenidate, cocaine, and MXE less potently inhibited DA uptake by T356 M hDAT, while citalopram more potently inhibited uptake. The differences in IC50 values between T356 M and WT hDAT were considerable (3–45 fold). As such, the presence of this polymorphism could affect treatment efficiency with these substances as well as susceptibly for toxicity and addiction for individuals carrying this polymorphism.